Hydrodynamic Velocity Performance of Turbine-Type and Thruster-Type Conduction-Mode MHD Drives under Electrical Voltage Variation in Seawater - Philipus Darwin Anwar; Aaron Bentlee Chow; Erasmus Alvaro Wirosasmita; Agus Jarwanto; Carolina Widya Maryana (Journal of Business, Social and Technology, 2026)
Background: Indonesia's maritime transportation sector is heavily dependent on fossil fuels, driving interest in clean propulsion alternatives. The magnetohydrodynamic (MHD) drive, which generates thrust via Lorentz force acting on conductive seawater (F = BIL), offers a propeller-free, low-noise option. However, comparative performance data for turbine-type versus thruster-type conduction configurations remain limited. Objective: To quantify the effect of electrical voltage variation (3–15 V) on hydrodynamic velocity and to compare the propulsion performance of turbine-type and thruster-type MHD drive configurations in seawater. Methods: A controlled laboratory experiment applied DC voltage at five levels (3, 6, 9, 12, and 15 V) to each prototype in a seawater medium. Velocity was calculated as v = s/t over a fixed 10 cm distance. Lorentz force was computed using B= μ₀I/2πa and F = BIL sin θ. Results: Turbine velocity ranged from 0.83 cm/s at 3 V to 3.38 cm/s at 15 V; thruster velocity ranged from 0.70 cm/s to 2.62 cm/s over the same range. The turbine consistently outperformed the thruster at all voltages. Lorentz force was 1.76 × 10⁻⁷ N (turbine) versus 1.48 × 10⁻⁷ N (thruster) at peak current, consistent with the velocity hierarchy. Conclusion: Both electrical voltage and drive configuration significantly affect MHD propulsion performance. The turbine-type configuration is superior due to its nozzle geometry, which enhances directed flow, supporting its potential for energy-efficient marine propulsion applications.